Structure and thermochromic properties of Mo-doped VO2 thin films deposited by sol–gel method. Issue 4 (3rd April 2019) - Dang, Yuanyuan; Wang, Danping; Zhang, Xin; Ren, Lin; Li, Binyu; Liu, Juncheng
Abstract: Thermochromic VO2 thin films were prepared on quartz substrates with sol–gel method. After the Vanadium oxide films were annealed at 550 °C for 4 h in a tube furnace within a nitrogen atmosphere, Mo 6+ -doped VO2 films were obtained. As the concentration of Mo 6+ increased, the primary diffraction peaks shifted slightly toward the small angle, and the VO2 grains became larger and larger. The XPS demonstrated that the valence of vanadium was mainly +4 and molybdenum was mainly +6. Finally, it is found that the effect of Mo 6+ doping decreases T c by approximately 5 °C per 1 at. % on average.